Soil organic matter dynamics in paired rangeland and cropland toposequences in North Dakota - Schimel, D.S.; Coleman, D.C.; Horton, K.A.
The effects of cultivation and erosion on organic matter transformations were studied by systematically sampling slope positions on three paired rangeland and cropland toposequences. The toposequences were on differing parent materials, sandstone, siltstone and shale in southwestern North Dakota. Soils weathered from the three parent materials were all Haploborolls or Argiborolls but differed in texture and solum depth. Carbon, nitrogen, phosphorus and soil loss have been previously measured. Microbial biomass C and N by chloroform fumigation, mineralizable C and N during 10, 20 and 60 day incubations, and organic C and N content were measured. Decreases in the above soil properties occurred in cropland soils, but the proportion of organic N mineralized increased. Biomass and mineralizable C and N concentrations were correlated with organic C and N concentrations, rather than with total accumulation in the profile. Total accumulation and proportion of N mineralized were correlated with clay content. Changes in respiration: mineralization, mineralization:biomass and microbial C:N ratios suggested differences in substrate and microbial population composition between rangeland and cropland. Microbial biomass and mineralization rates did not vary with slope position, but parent material had significant effects. The siltstone site which had the highest soil losses began with the highest microbial biomass and mineralizable C and N concentrations and had the highest losses. The sandstone site suffered high soil but low OM constituent losses whereas the shale site suffered low soil and OM constituent losses. The sites can be classified in terms of their response to perturbation using concepts of "resistance" and "resilience" from ecosystem theory. The sandstone and shale sites may both be considered "resistant" with respect to agricultural perturbation, whereas the sittstone site was not.